Neuroinflammation: effect of surgical stress compared to anaesthesia and effect of physostigmine - Plaschke, Konstanze; Weigand, Markus A.; Fricke, Fabia; Kopitz, Jürgen (Neurological research, 2016)
Objectives: Surgical interventions can cause systemic postoperative inflammation, which in turn can induce neuroinflammation. A close link between immune reaction and cholinergic metabolism has been postulated. Pharmacological enhancement of cholinergic activity by administering physostigmine is known to induce protective effects. It is not known, however, whether physostigmine has an impact on postoperative inflammation and acetylcholine metabolism after a partial liver resection (PLR) surgery.Methods: Rats (n = 100) underwent a PLR or sham surgery. Rats were investigated before the intervention and 120 min and 24 h postoperatively. The control group only received sevoflurane anaesthesia. Half of each treatment group received a single intraoperative dose of physostigmine, whereas the others were given placebo.Acetylcholine (ACHE) and butyrylcholinesterase (BuCHE) activity and IL1β, IL6 and corticosterone levels were measured in rat plasma and brain. Acetylcholine (ACH) concentrations were determined additionally in cerebral tissue.Results: Surgical interventions induced a peripheral stress reaction, which was characterized by an increase (p < 0.05) in pro-inflammatory cytokines, cholinergic esterases and corticosterone at 120 min postoperatively in rat blood and in cerebral tissue. At 24 h postoperatively, all measured cerebral parameters reached control values. In blood, IL1β and BuCHE were still increased, suggesting they are peripheral markers of a stress reaction. The reduced cerebral acetylcholine is increased after physostigmine administration. Furthermore, physostigmine reduced IL1β (p < 0.05).Conclusion: We show in this observational study that a single intraoperative dose of physostigmine produced a sustained anti-inflammatory effect in rat blood and brain up to 120 min postoperatively, which was especially pronounced under the condition of PLR surgery.